Factors That Affect The Tendency of Accounting Fraud (Case Study At BUMN Banks In Kuningan Regency ) - Dikdik Harjadi; Amir Hamzah; Dewi Fatmasari (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2022)
This study aims to find out and analyze the factors that affect the tendency of accounting fraud at BUMN banks in Kuningan Regency. This study uses descriptive and verifiative methods. Sampled in this study as many as 95 employees of BUMN banks in Kuningan Regency. The data analysis technique used is multiple regression analysis using Lisrel. The results showed that information asymmetry has a positive effect on the tendency of accounting fraud, spiritual intelligence negatively affects the tendency of accounting fraud, the morality of the leadership has no effect on the tendency of accounting fraud, the suitability of compensation negatively affects the tendency of accounting fraud and good governace has no effect on the tendency of accounting fraud.Â Keywords: information asymmetry, spiritual intelligence, morality of the leadership, the suitability of compensation, good governace, the tendency of accounting fraud